A Pair of Cobalt(III/IV) Terminal Imido Complexes. Issue 30 (18th June 2021) - Mao, Weiqing; Fehn, Dominik; Heinemann, Frank W.; Scheurer, Andreas; Munz, Dominik; Meyer, Karsten
Abstract: The reaction of the cobalt(I) complex [(TIMMN mes )Co I ](BPh4 ) (2 ) (TIMMN mes =t ris‐[2‐(3‐mesitylim idazolin‐2‐ylidene)m ethyl]amin e) with 1‐adamantylazide yields the cobalt(III) imido complex [(TIMMN mes )Co III (NAd)](BPh4 ) (3 ) with concomitant release of dinitrogen. The N‐anchor in diamagnetic 3 features an unusual, planar tertiary amine, which results from repulsive electrostatic interaction with the filled d(z 2 )‐orbital of the cobalt ion and negative hyperconjugation with the neighboring methylene groups. One‐electron oxidation of 3 with [FeCp2 ](OTf) provides access to the rare, high‐valent cobalt(IV) imido complex [(TIMMN mes )Co IV (NAd)](OTf)2 (4 ). Despite a half‐life of less than 1 h at room temperature, 4 could be isolated at low temperatures in analytically pure form. Single‐crystal X‐ray diffractometry and EPR spectroscopy corroborate the molecular structure and the d 5 low‐spin, S= 1 / 2, electron configuration. A computational analysis of 4 suggests high covalency within the Co IV =NAd bond with non‐negligible spin density located at the imido moiety, which translates into substantial triplet nitrene character. Abstract : Straightforward access to a cobalt(IV) terminal imido complex was provided by one‐electron oxidation of a cobalt(III) terminal imido precursor. The cobalt(IV) monoimido complex could be isolated at low temperatures in analytically pure form. Single‐crystal X‐ray diffractometry and EPR spectroscopy corroborate the molecular structure and the d 5 low‐spin, S= 1 / 2, electron configuration.